Competency achievement indicators in Indonesian high school electronic school books: Overview of the development of creative-innovative thinking aspects - Imam Safi'i; Wini Tarmini; Ade Hikmat; Prima Gusti Yanti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Creative-innovative thinking is an important competency to be developed in students so that they can be equipped in solving various challenges they face. One of the efforts to increase student competence can be done through the provision of textbooks. The purpose of writing this article is to explain the results of research on creative-innovative aspects which are indicators of competency development in high school electronic school books. The method used is content analysis, namely through excavation and in-depth meaning of various data on creative-innovative aspects in indicators of achievement of Indonesian high school electronic schoolbook competencies. The source of the data in this study was the Indonesian language electronic school book for SMA class X, XI, and XII published by the Ministry of Education and Culture. Based on the research that has been done, data is obtained, that in general the development of indicators of competency achievement has been associated with various creative-innovative aspects. However, there are still some creative-innovative aspects that have not been developed optimally, namely expressing creative ideas conceptually and practically, using failure as learning, and adapting and contributing to new situations. Each of these aspects is only 2.5%, 1.0%, and 0.5% of the total competency development indicators in the Indonesian high school electronic school book. The results of this study can be used as a basis for further development of creative-innovative aspects in Indonesian language textbooks.